"Masked crusader": a case study of "crime-fighting" activities by a "real-life superhero". Issue 2 (8th June 2015) - Iouchkov, Vladislav; Birch, Philip
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine informal social control, vigilantism, and bystander intervention with reference to the Real-Life Superhero (RLSH) movement/community. Design/methodology/approach – This is a qualitative case study in which an in-depth semi-structured interview was conducted with a member of the RLSH community. Findings – This paper conceptualises RLSH activity as a novel approach to informal social control and bystander intervention, whilst revealing the inaccuracy of the media-imposed "vigilante" stigma attributed to RLSHs. Research limitations/implications – Clarifying the goals and methods of RLSHs as striving to be pro-social and law-abiding in nature creates an avenue for dialogue between RLSHs and local justice agencies to establish a working partnership for community safety, thereby mediating interactions between informal and formal agents of social control. Practical implications – Justice agencies to engage with all individuals and groups who are performing community safety/crime prevention functions in a more effective and inclusive way. To ensure formal and informal mechanisms of social control, and the wider community, recognise, and legitimise the RLSH movement in community safety policy and practice. Reconsider the use of the term "vigilantism" and how it is it applied to individuals and community groups involved in community safety policy and practice. This case study presents a unique approach to community safety and crime prevention that can be extended within this public safety philosophy and practice. Originality/value – This study is a contribution to a small but growing body of research concerning the RLSH movement/community.